Perancangan Dan Pembuatan Cetakan Ornamen Teralis Dari Aluminium - Muhammad Arkan; Sailon; Syamsul Rizal (PT. Hasba Edukasi Mandiri, 2025)
The metal casting process is the process of pouring molten metal produced from melting into a mold at the melting temperature of the metal. Aluminum casting is generally done by the Sand Casting method, using a sand mold. Aluminum itself is a metal that is often used for various purposes, ranging from household appliances, construction, to automotive components and various other applications. This study focuses on the design and manufacture of aluminum trellis ornament molds, which are intended to improve production efficiency and the quality of the final product. The data processing method used in this study is the FEA (Finite Element Analysis) method. From the results of the analysis carried out through the FEA (Finite Element Analysis) analysis method that has been applied, it can be concluded that the stress distribution in the trellis ornament mold increases significantly with an increase in load from 50kg to 150kg. The results of the study also show that the mold is able to withstand loads of up to 150kg with tension and exceeding that which is within the safe limit. From the results of this study, it is recommended to make recommendations for improvements including the use of alternative materials with higher strength, redesigning the geometry of the mold to reduce stress concentration, and optimizing the process. Therefore, the results of this research are expected to be used in the future as a reference or literature to increase insight into the development of stronger and more efficient aluminum trellis ornament molds.